2019
DOI: 10.1002/ijc.32041
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐PD‐1/PD‐L1 therapy augments lenvatinib's efficacy by favorably altering the immune microenvironment of murine anaplastic thyroid cancer

Abstract: Patients with anaplastic thyroid cancer (ATC) have an extremely poor prognosis despite multimodal therapy with surgery and chemoradiation. Lenvatinib, a multi-targeted tyrosine kinase inhibitor, as well as checkpoint inhibitors targeting the programmed cell death pathway, have proven effective in some patients with advanced thyroid cancer. Combination of these therapies is a potential means to boost effectiveness and minimize treatment resistance in ATC. We utilized our novel immunocompetent murine model of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 47 publications
(56 reference statements)
3
69
0
Order By: Relevance
“…Indeed, PDL1 immunoreactivity is evident in a subset of ATCs, often displaying strong and widespread expression in approximately 80% of tumor cells-mirroring the findings in our case [18,19]. The prognostic significance of this expression pattern is, however, not known, and ATC-related studies with PDL1 inhibitors in the clinical setting are scarce [20,21], although studies with animal models seem promising [22,23].…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, PDL1 immunoreactivity is evident in a subset of ATCs, often displaying strong and widespread expression in approximately 80% of tumor cells-mirroring the findings in our case [18,19]. The prognostic significance of this expression pattern is, however, not known, and ATC-related studies with PDL1 inhibitors in the clinical setting are scarce [20,21], although studies with animal models seem promising [22,23].…”
Section: Discussionsupporting
confidence: 77%
“…Many antineoplastic drugs studies had shown reduced proportion of CD11b + Gr-1 + cells in tumor-bearing mice after drug treatment (Fleming et al, 2018), in addition to lenvatinib (Gunda et al, 2019) and gemcitabine (Mu et al, 2019). Frequency of CD11b + Gr-1 + cells was considered as an important factor to promote tumor progression and tumor cell resistance, and as an independent factor to evaluate the efficacy and prognosis of anti-tumor therapy (Ai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many antitumor drugs exhibited the abilities to reduce the accumulation of CD11b + Gr-1 + cells and immunosuppression of a tumor-bearing host (Kim and Kim, 2019). However, gemcitabine increased CD11b + Ly6C high cells infiltration in bladder cancer tissues (Mu et al, 2019) and lenvatinib was associated with increased tumor-infiltrating and circulating CD11b + Gr-1 + cells (Gunda et al, 2019). In our research, we observed changes in the proportion of CD11b + Gr-1 + cells and subsets in the spleen and bone marrow, which were most relevant to recruitment and generation of MDSCs.…”
Section: Jhd Increases the Proportion Of Cd11c + And Cd11b + Gr-1 + Cmentioning
confidence: 99%
“…Several studies using immunocompetent murine models of thyroid cancer have shown effective results using either BRAF inhibition or the multikinase (VEGFR, FGFR, PDGFR, RET) inhibitor lenvatinib together with immune checkpoint PD-1/PD-L1 blockade. [16][17][18] However, in these preclinical models, despite significantly prolonged survival and reduced tumor growth, mice were not cured of their disease, suggesting that there remains the opportunity to test additional drugs in combination strategies. Immunohistochemical analysis of patient tumor samples shows that 23%-81.3% of ATC and 25% of PDTC express PD-L1, although the data supporting a link between PD-L1 expression and disease aggression are conflicting.…”
Section: Open Accessmentioning
confidence: 99%